Two different doses of caudal neostigmine co-administered with levobupivacaine produces analgesia in children - Karaaslan, Kazim; Gulcu, Nebahat; Ozturk, Hayrettin; Sarpkaya, Ali; Colak, Cemil; Kocoglu, Hasan (Wiley-Blackwell, 2009)
This study was aimed to evaluate the analgesic efficacy, duration of analgesia, and side effects of two different doses of caudal neostigmine used with levobupivacaine in children. Sixty boys, between 5 months and 5 years, undergoing genito-urinary surgery were allocated randomly to one of three groups (n = 20 each). Group I patients received caudal 0.25% levobupivacaine (1 ml.kg(-1)) alone. Groups II and III patients received neostigmine (2 and 4 mu g.kg(-1) respectively) together with levobupivacaine used in the same dose as Group I. Pain scores were assessed using Children's and Infant's Postoperative Pain Scale (CHIPPS) at 15th (t(1)) min after arrival to postanesthetic care unit, and 1st (t(2)), 2nd (t(3)), 3rd (t(4)), 4th (t(5)), 8th (t(6)), 16th (t(7)), and 24th (t(8)) hour postoperatively. Duration of analgesia, amount of additional analgesic (paracetamol), score of motor blockade and complications were recorded for 24 h postoperatively, and compared between groups. CHIPPS scores were higher during t(2), t(3), t(6), t(7) and t(8) periods, duration of analgesia was shorter, and total analgesic consumption was higher in Group I compare to neostigmine groups (P < 0.05). Duration of postoperative analgesia and total analgesic consumption were similar in Groups II and III (P > 0.05). Adverse effects were not different between three groups. Caudal neostigmine in doses of 2 and 4 mu g.kg(-1) with levobupivacaine extends the duration of analgesia without increasing the incidence of adverse effects, and 2 mu g.kg(-1) seems to be the optimal dose, as higher dose has no further advantages.
Keywords: levobupivacaine; neostigmine; caudal block; postoperative analgesia